2022
DOI: 10.1186/s12871-022-01707-4
|View full text |Cite|
|
Sign up to set email alerts
|

Lung ultrasound is non-inferior to bronchoscopy for confirmation of double-lumen endotracheal tube positioning: a randomized controlled noninferiority study

Abstract: Background Appropriate placement of left-sided double-lumen endotracheal tubes (LDLTs) is paramount for optimal visualization of the operative field during thoracic surgeries that require single lung ventilation. Appropriate placement of LDLTs is therefore confirmed with fiberoptic bronchoscopy (FOB) rather than clinical assessment alone. Recent studies have demonstrated lung ultrasound (US) is superior to clinical assessment alone for confirming placement of LDLT, but no large trials have comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…One study [ 24 ] was excluded because ultrasound examination was carried out after correct placement of DLT, and two [ 25 , 26 ] studies were excluded for not using ultrasound to assess the DLT position. Finally, eight studies [ 14 , 15 , 20 , [27] , [28] , [29] , [30] , [31] ] were included in the quantitative analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study [ 24 ] was excluded because ultrasound examination was carried out after correct placement of DLT, and two [ 25 , 26 ] studies were excluded for not using ultrasound to assess the DLT position. Finally, eight studies [ 14 , 15 , 20 , [27] , [28] , [29] , [30] , [31] ] were included in the quantitative analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [ 14 , 15 , 20 , 28 , 29 ] targeted left-sided DLT placement; one study [ 30 ] inspected bilateral DLT intubation; and the remaining two studies [ 27 , 31 ] did not specify the type of DTL used, as the side of DLT was selected according to the judgement of anesthesiologists who performed the intubation. The diagnostic accuracy of lung ultrasound was compared with that of clinical evaluations in seven studies [ 14 , 15 , 20 , 27 , 28 , 30 , 31 ] and FOB in one study [ 29 ]. The tube position was determined by FOB [ 14 , 20 , 27 , 28 , 30 , 31 ] or visualization of lung collapse during surgery [ 15 , 29 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the current study showed substantial agreement between LUS and FOB (κ = 0.705) and poor agreement between auscultation and FOB (κ = 0.104). Kanavitoon et al (3) reported that, as demonstrated by surgical grading, LUS is superior to FOB for obtaining sufficient lung collapse after the correct insertion of a DLT. They concluded that LUS was non-inferior to FOB in detecting proper tube position with subsequent adequate lung collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Misplacement of the DLT can result in inadequate nonventilated (operative) lung deflation, insufficient lung ventilation, and hypoxemia (2). Therefore, optimal DLT positioning is essential for efficient lung isolation during thoracic procedures with fewer intraoperative complications (3).…”
Section: Introductionmentioning
confidence: 99%